Natural History of Cryptosporidiosis in a Longitudinal Study of Slum-Dwelling Bangladeshi Children: Association with Severe Malnutrition. - Poonum S Korpe; Rashidul Haque; Carol Gilchrist; Cristian Valencia; Feiyang Niu; Miao Lu; Jennie Z Ma; Sarah E Petri; Daniel Reichman; Mamun Kabir; Priya Duggal; William A Petri (Public Library of Science (PLoS), 2016)
BACKGROUND:Cryptosporidiosis is a common cause of infectious diarrhea in young children worldwide, and is a significant contributor to under-five mortality. Current treatment options are limited in young children. In this study, we describe the natural history of Cryptosporidium spp. infection in a birth cohort of children in Bangladesh and evaluate for association with malnutrition. METHODOLOGY/PRINCIPAL FINDINGS:This is a longitudinal birth cohort study of 392 slum-dwelling Bangladeshi children followed over the first two years of life from 2008 to 2014. Children were monitored for diarrheal disease, and stool was tested for intestinal protozoa. Anthropometric measurements were taken at 3-month intervals. A subset of Cryptosporidium positive stools were genotyped for species and revealed that C. hominis was isolated from over 90% of samples. In the first two years of life, 77% of children experienced at least one infection with Cryptosporidium spp. Non-diarrheal infection (67%) was more common than diarrheal infection (6.3%) although 27% of children had both types of infection. Extreme poverty was associated with higher rates of infection (chi-square, 49.7% vs 33.3%, p = 0.006). Malnutrition was common in this cohort, 56% of children had stunted growth by age two. Children with Cryptosporidium spp. infection had a greater than 2-fold increased risk of severe stunting at age two compared to uninfected children (odds ratio 2.69, 95% CI 1.17, 6.15, p = 0.019) independent of sex, income, maternal body-mass index, maternal education and weight for age adjusted z (WAZ) score at birth. CONCLUSIONS/SIGNIFICANCE:Cryptosporidium infection is common (77%) in this cohort of slum-dwelling Bangladeshi children, and both non-diarrheal and diarrheal infections are significantly associated with a child's growth at 2 years of age.